2023
DOI: 10.1021/jacs.3c07941
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt–Sulfur Coordination Chemistry Drives B12 Loading onto Methionine Synthase

Romila Mascarenhas,
Arkajit Guha,
Zhu Li
et al.

Abstract: Cobalt−sulfur (Co−S) coordination is labile to both oxidation and reduction chemistry and is rarely seen in nature. Cobalamin (or vitamin B 12 ) is an essential cobalt-containing organometallic cofactor in mammals and is escorted via an intricate network of chaperones to a single cytoplasmic target, methionine synthase. In this study, we report that the human cobalamin trafficking protein, MMADHC, exploits the chemical lability of Co−S coordination for cofactor off-loading onto methionine synthase. Cys-261 on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 51 publications
0
0
0
Order By: Relevance
“…31,32 To further elucidate the mechanism for electrocatalytic disulfide reduction, we focused on VB 12 since several potential catalytic intermediates have been reported. 33,34 We observed that the reaction between the electrochemically generated reduced Co(I) species and excess 1 yields the previously characterized Co(III)-cysteine adduct by UV-Vis spectroscopy (Figure 2B). 35 Based on the established VB 12 reactivity, [36][37][38] the Co(I) most likely reacts via nucleophilic attack on the disulfide, pushing the two electrons of the disulfide bond to the leaving thiolate.…”
mentioning
confidence: 56%
“…31,32 To further elucidate the mechanism for electrocatalytic disulfide reduction, we focused on VB 12 since several potential catalytic intermediates have been reported. 33,34 We observed that the reaction between the electrochemically generated reduced Co(I) species and excess 1 yields the previously characterized Co(III)-cysteine adduct by UV-Vis spectroscopy (Figure 2B). 35 Based on the established VB 12 reactivity, [36][37][38] the Co(I) most likely reacts via nucleophilic attack on the disulfide, pushing the two electrons of the disulfide bond to the leaving thiolate.…”
mentioning
confidence: 56%